Rapid and complete paraffin removal from human tissue sections delivers enhanced Raman spectroscopic and histopathological analysis. Issue 4 (2nd January 2020) - Gaifulina, Riana; Caruana, Daren J.; Oukrif, Dahmane; Guppy, Naomi J.; Culley, Siân; Brown, Robert; Bell, Ian; Rodriguez-Justo, Manuel; Lau, Katherine; Thomas, Geraint M. H.
Abstract : A simple method completely removes contaminating paraffin from samples for clinical Raman and enhanced immunohistological analysis. Abstract : Incomplete removal of paraffin and organic contaminants from tissues processed for diagnostic histology has been a profound barrier to the introduction of Raman spectroscopic techniques into clinical practice. We report a route to rapid and complete paraffin removal from a range of formalin-fixed paraffin embedded tissues using super mirror stainless steel slides. The method is equally effective on a range of human and animal tissues, performs equally well with archived and new samples and is compatible with standard pathology lab procedures. We describe a general enhancement of the Raman scatter and enhanced staining with antibodies used in immunohistochemistry for clinical diagnosis. We conclude that these novel slide substrates have the power to improve diagnosis through anatomical pathology by facilitating the simultaneous combination of improved, more sensitive immunohistochemical staining and simplified, more reliable Raman spectroscopic imaging, analysis and signal processing.